An investigation of ultrasound effect on microalgal cell integrity and lipid extraction efficiency - Keris-Sen, Ulker D.; Sen, Unal; Soydemir, Gulfem; Gurol, Mirat D. (Elsevier Sci Ltd, 2014)
In this study, different ultrasound power intensities (0.1-0.5 W mL(-1)) were applied at a frequency of 30 kHz and for durations of 5-60 min to mixed microalgal cultures, one cultivated in BG11 medium, and the other in secondary effluent wastewater. The ultrasonic effect on cell disruption was revealed by increased concentrations of protein and carbohydrate released into the solution, and a decreased concentration of total suspended solids in cell suspension. The highest intercellular material release was achieved at an ultrasonic energy intensity of 0.4 kWh L-1, while the effect of ultrasound on cell disruption was reduced at higher energy intensities. Additionally, the ultrasonic effect on lipid extraction efficiency was studied in the presence of two different solvents, n-hexane and chloroform/methanol mixture. The application of ultrasound at 0.4 kWh L-1, provided 1.5-2.0-fold increase in lipid extraction yields in the presence of the solvents. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Ultrasound; Microalgae; Secondary effluent; Total lipids; Lipid extraction